Record of Himalayan Serow (Capricornis sumatraensis ssp. thar Hodgson, 1831) in Manas Tiger Reserve, Assam, India - Deka, Jyotishman; Das, Umesh; Islam, Nazrul; Sarmah, Amal Chandra (Indian Forester, 2021)
No Abstract.